Analisis Pemberian Kompensasi dan Fasilitas Lingkungan Kerja Fisik dalam Meningkatkan Kinerja Pegawai Kantor Desa Bungaya, Kabupaten Karangasem - Juliantari, Fiolina; Indrayani, Luh (Universitas Pendidikan Ganesha, 2023)
The purpose of this study is to determine the compensation and physical work environment facilities in improving the performance of Bungaya Village Office employees. This research uses a qualitative descriptive approach with a case study method. The subjects of this study used 6 informants, and the objects were compensation, physical work environment, and employee performance at the Bungaya Village Office. The data collection method used observation, in-depth interviews with informants, and documentation. The data analysis technique used in this study is a qualitative analysis of the Miles and Huberman model, which started by collecting, reducing, presenting, and drawing conclusions of the data. The data validity technique in this study used source triangulation. The results showed that the delay and low compensation received by employees affected a decrease in employee performance, while for inadequate physical work environment facilities resulted in employee delays in working, thus affecting a decrease in the employee's performance.